Efficient Catalytic Conversion of 5‐Hydroxymethylfurfural to 2, 5‐Furandicarboxylic Acid over Ruthenium Cluster‐Embedded Ni(OH)2 Catalyst. Issue 16 (6th July 2022) - Chai, Xinyu; Jiang, Kaiyue; Wang, Jianying; Ren, Zhouhong; Liu, Xi; Chen, Liwei; Zhuang, Xiaodong; Wang, Tianfu
Abstract: 5‐Hydroxymethylfurfural (HMF) can be oxidized to 2, 5‐furandicarboxylic acid (FDCA) for the production of biorenewable plastics to replace fossil resourced polyethylene terephthalate (PET). Development of a highly efficient electrocatalyst using renewable electricity as energy input is highly desired. In this work, Ru cluster‐embedded Ni(OH)2 nanosheets [Ru/Ni(OH)2 ] were synthesized and exploited as electrochemical catalysts for the conversion of HMF to FDCA. Ru/Ni(OH)2 exhibited significantly improved current density (40 mA cm −2 at 1.41 V vs. reversible hydrogen electrode) of over 7.7 times in comparison with Ni(OH)2, and nearly 100 % conversion degree for HMF and 98.5 % selectivity towards FDCA were obtained. Operando Raman experiments revealed the catalysis was facilitated by the interconversion between Ni 3+ and Ni 2+ . Density functional theory calculations further revealed the effect of Ru clusters of Ni(OH)2, thereby promoting HMF adsorption capacity on Ni sites to boost HMF oxidation activity. This work provides a novel strategy using Ru clusters to modify earth abundant Ni based catalyst for HMF oxidation to obtain high‐value biomass‐derived products. Abstract : Electrooxidation : Ru clusters are uniformly dispersed on the Ni(OH)2 nanosheets and bonded with Ni(OH)2 substrates through Ru−O−Ni interaction. They are effective to adjust the structural and electronic structure of nanosheets, inducing the generation of abundant high‐valence nickel sites and improving the activity of electrooxidation of 5‐hydroxymethylfurfural to 2, 5‐furandicarboxylic acid.